Identifying transit deserts in major Texas cities where the supplies missed the demands - Jiao, Junfeng (Journal of Transport and Land Use, 2017)
Coined by the author, the concept “transit desert” is developed from the now common concept of a “food desert,” which is an area where there is limited or no access to fresh food (Clark et al. 2002; Jiao et al. 2012; Whelan et al. 2002; Wrigley 1993; Wrigley et al. 2002). The food desert concept has received a lot of attention and influenced planning policies and practices. By applying the same idea to transit systems within urban areas, geographic areas can be identified where there is a lack of transit service. This involves identifying the transit dependent populations as a measure of transit demand, calculating the transit supply, and then subtracting the supply from the demand to measure the gap (Jiao & Dillivan 2013). In detail, transit dependent populations are those who might require transit service to get around more than other people. The transit supply is measured by aggregating a number of criteria that contribute to better transit access and measured within a designated geographic area. Transit deserts are defined as areas where the transit demand is significantly greater than the supply.